PENYELESAIAN SENGKETA PERIKANAN DI LAUT LEPAS MENURUT HUKUM INTERNASIONAL - Veriena J. B. Rehatta (SASI, 2014)
The benefits are so great on marine management must make all parties or nations wanted to do the exploration and exploitation of these resources, including sea off, so sometimes causing disputes between parties including between countries in implementing management. Dispute can be resolved nationally and internationally, depending of the parties therein. International dispute resolution fisheries that occur at sea off can be resolved amicably between the two sides, but when the agreements of peace between the parties can not be reached, the dispute settlement procedure of fisheries at sea off can be done by 4 ways namely through the International Tribunal for the Law of the Sea, the International Court of Justice, or the Special Arbitration Procedure Arbitration and Conciliation Consiliation.